Evaluation of pre-diploma students using fuzzy approach / Zamali Tarmudi, Mazalan Sarahintu and Ajis Lepit - Tarmudi, Zamali; Sarahintu, Mazalan; Lepit, Ajis (Universiti Teknologi MARA, Perlis, 2015)
This paper discusses the comprehensive evaluation of Pre-Diploma (Science) students in recent semesters using fuzzy approach. It focuses on how we can select the best students based on both academic performance and soft skills for university recognition purposes. The approach utilizes membership functions to derive the membership values for the entire course which registered for first semester. Then the approach employs the intersection of fuzzy goals and constraints concept to identify the best students among the best in terms of academic performance, soft skills as well as their attitude. A case study was conducted based on session intake of November 2013 - March 2014. It was found that our proposed approach has unique advantage in the sense that it can distinguish clearly for every single score marks obtained by the students. Also, the results show that the approach is highly beneficial for problem solving under uncertainty data sets environment.